Mediating role of consumer identity between factors influencing purchase intention and actual behavior in organic food consumption in Thailand - Nitima Aungatichart; Aya Fukushige; Mayuree Aryupong (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2020)
The aims of this research are toexplore the relationship between the factors influencing purchase intention and actual behaviors of Thai consumers of organic food, and to observe the mediating role of consumer identity between the factors:attitude towardorganic food, subjective norm, and perceived behavioral control,and purchase intentions.Thetheoryof planned behavior(TPB)was adoptedas a theoretical framework which containedthe role of consumer identity as a mediator. Datawascollected from400Thaiconsumers of organic foods. Structural equation modelingwas usedto analyze the data throughAMOSpackage. The results of the data analysis indicate that the consumer identityplays a full mediating role between independent variables (i.e. health concern, subjective norm, organic food familiarity and organic food literacy) and purchaseintention. The organic food literacy is the main determinant of consumer identity with the highest coefficient value, whilst the organic food familiarity was placed as the second important determinant of consumer identity. Moreover, the results highlight the strong influence of intention on actual behavior of organic food purchase. Accordingly, this study thoroughly captures the TPB model and strengthensit by confirmingrelationship between purchase intention and actual purchase behaviors in organic food consumption and revealed that actual purchase behavior is significantly affected bythepurchaseintention of Thai consumers of organic food.
Keywords: 330; organic food; consumer identity; health concern; food safety; ecological concerns; organic food familiarity; organic food literacy